Effect of intensification casting pressure on microstructure and mechanical properties of high pressure die casting AE81 magnesium alloy - Hecong Xie; Yongfeng Li; Jiangfeng Song; Hengrui Hu; Dongmei He; Chunyu Li; Bin Jiang; Dongxia Xiang; Fusheng Pan (Journal of Materials Research and Technology)
This paper investigates the effect of intensification casting pressure on the microstructure, defect distribution, and mechanical properties of high pressure die casting (HPDC) AE81 magnesium alloy. The findings indicate that with the increase in intensification casting pressure, the microstructural uniformity of HPDC AE81 magnesium alloy is significantly improved, accompanied by a refinement in grain size. Additionally, the area fraction of Externally solidified Crystals (ESCs) and the pores volume fraction are effectively reduced. Moreover, higher intensification casting pressure leads to a notable reduction in the number of internal pores, especially with the near complete disappearance of network shrinkage and gas pore. When an intensification casting pressure of 30 MPa is applied, the alloy exhibits excellent mechanical properties: the yield strength (YS) reaches 186 ± 3.5 MPa, the ultimate tensile strength (UTS) is 279 ± 2.3 MPa, and the elongation (EL) is 9.6 ± 0.8 %. It is noteworthy that the mechanical properties of HPDC AE81 magnesium alloy are significantly negatively correlated with the spatial distribution of internal ESCs and pores.